Does economics make you selfish? - Daniele Girardi; Sai Madhurika Mamunuru; Simon D. Halliday; Samuel Bowles (University of Massachusetts, Department of Economics, 2021)
It is widely held that studying economics makes you more selfish and politically conservative. We use a difference-in-differences strategy to disentangle the causal impact of economics education from selection effects. We estimate the effect of four different intermediate microeconomics courses on students' experimentally elicited social preferences and beliefs about others, and policy opinions. We find no discernible effect of studying economics (whatever the course content) on self-interest or beliefs about others' self-interest. Results on policy preferences also point to little effect, except that economics may make students somewhat less opposed to highly restrictive immigration policies.
Keywords: 330